Implementasi Permainan Balok Dalam Meningkatkan Aspek Perkembangan Kognitif Anak di Kelompok Bermain Kartini 1 Terpadu di Dusun Jambu Desa Beringin Kec Sajad - Herlina; Aslan; Sera Yuliantini (Tarbiya Islamica, 2023)
The aim of the research is to determine the implementation of block games in improving aspects of children's cognitive development in the Kartini 1 Integrated Play Group in Jambu Hamlet, Beringin Village and to determine the evaluation of block games in improving aspects of children's cognitive development in the Integrated Kartini 1 Play Group in Jambu Hamlet, Beringin Village, District. Sajad Academic Year 2022-2023. The primary data sources in this research are teachers and early childhood children. Data collection techniques include observation, interviews and documentation methods. The data analysis that researchers use after data collection consists of: data reduction, data display, verification and drawing conclusions. Meanwhile, to check the validity of the data, continuous observation, data triangulation and member checking are used. Research result; Implementation of block games to improve aspects of children's cognitive development in the Kartini 1 Integrated play group in Jambu Hamlet, Beringin Village. The teacher informs the children of the activities that will be carried out, the teacher tells the students how to carry out the block game, distributes the equipment for the block game to the students, guides and directs the children during the activity, the teacher will respond to the block game that has been arranged, the teacher asks what what children feel when playing with blocks, making observations and assessments. Evaluation of block games in improving aspects of children's cognitive development in the Kartini 1 Integrated play group in Jambu Hamlet, Beringin Village. The teacher assesses the child's development in playing with blocks, namely by the work made by the child, the teacher assesses from the questions given whether the child can answer the questions and mention the shape of the blocks the child is playing with, the teacher gives a task to the child to make a building from beam.